2003
DOI: 10.1007/s00428-003-0874-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the LGI1 gene product in astrocytic gliomas: downregulation with malignant progression

Abstract: Loss of heterozygosity in the long arm of chromosome 10q is a frequent event in gliomas. It may involve the LGI1/epitempin gene, which is located in chromosomal region 10q23 approximately 24 and has been proposed to encode a tumor suppressor inactivated in the progression of brain tumors. Nevertheless, so far no data are available demonstrating that the reduced expression of the LGI1 transcript in high-grade astrocytic tumors indeed results in a decreased level of LGI1 protein in the tumor cells. Thus, the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…In 16 (45.7%) of 35 GBMs, LGI1 expression was very low or absent and was completely absent in all cell lines. In only two of 35 low-grade gliomas, LGI1 expression was decreased or absent, while in other cases, expression levels were comparable to normal brain (two samples examined), confirming previous data (Besleaga et al, 2003;Chernova et al, 1998). (See supplementary data, Fig.…”
Section: Lgi1 Expression Is Often Low In Malignant Gliomassupporting
confidence: 90%
“…In 16 (45.7%) of 35 GBMs, LGI1 expression was very low or absent and was completely absent in all cell lines. In only two of 35 low-grade gliomas, LGI1 expression was decreased or absent, while in other cases, expression levels were comparable to normal brain (two samples examined), confirming previous data (Besleaga et al, 2003;Chernova et al, 1998). (See supplementary data, Fig.…”
Section: Lgi1 Expression Is Often Low In Malignant Gliomassupporting
confidence: 90%
“…In this cell line there is no normal copy of chromosome 10, which suggested that the translocation breakpoint might affect expression of the remaining copy of gene(s) located at the 10q24 breakpoint. In support of this, it has now been demonstrated by two groups that LGI1 is expressed at detectable levels in low grade gliomas but not in high grade gliomas (Chernova et al, 1998;Besleaga et al, 2003). The final stage of glioma progression gives rise to the highly invasive glioblastoma multiforme (GBM).…”
Section: Introductionmentioning
confidence: 89%
“…The downregulation of LGI1 might result in the increase of MPP expression supporting tumor growth and metastasis formation. These findings raised the possibility that the tumor suppressor function of LGI1 might impede malignant development, thus it was proposed to function as a type-II tumor suppressor gene (Besleaga et al, 2003).…”
Section: Type-ii Tumor Suppressormentioning
confidence: 99%
“…Immunohistochemistry and mRNA analysis showed that LGI1 levels are very low or completely absent in most tumor tissues and in several cancer cell lines including, www.intechopen.com glioblastoma, neuroblastoma, melanoma and breast, furthermore the decrease of LGI1 expression shows a significant correlation with the grade of malignancy of astrocytic gliomas (Rossi et al, 2005;Besleaga et al, 2003). DNA microarrays, SAGE and EST number suggest low or absent expression in the majority of tumor tissues (see Gabellini, 2007).…”
Section: Expression In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation